1997
DOI: 10.1046/j.1365-2362.1997.1220672.x
|View full text |Cite
|
Sign up to set email alerts
|

Does hypercalcaemia or calcium antagonism affect human melatonin secretion or renal excretion?

Abstract: Patients with primary hyperparathyroidism have higher serum melatonin concentrations during active disease than after surgical cure. Whether this is caused by hypercalcaemia per se, increased parathyroid hormone secretion or other mechanisms is unknown. We decided to elucidate whether exogenous hypercalcaemia influences melatonin secretion. For this purpose, eight healthy volunteers were infused with calcium and saline on separate days and in random order (experiment A). Hypercalcaemia inhibited nocturnal mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In a previous study we showed that exogenous hypercalcemia causes impaired MT secretion (Wikner et al, 1997), whereas other researchers have reported that endogenous hypercalcemia might have opposite effect (Brismar et al, 1987). The s-ionized calcium level was normal in the group of patients investigated in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…In a previous study we showed that exogenous hypercalcemia causes impaired MT secretion (Wikner et al, 1997), whereas other researchers have reported that endogenous hypercalcemia might have opposite effect (Brismar et al, 1987). The s-ionized calcium level was normal in the group of patients investigated in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…It was suggested that hypercalcemia itself provokes the increase of melatonin. In volunteers Wikner et al (1997) proved that indeed exogenous hypercalcaemia influenced melatonin, increased its secretion and serum level by 20% but left urinary melatonin excretion unaffected.…”
Section: Abmentioning
confidence: 95%
“…The pathophysiological mechanism behind a disturbed circadian rhythm of melatonin secretion is not known. Factors such as magnitude of surgery [12,48], anesthesia [64], perioperative administration of certain drugs (benzodiazepines [65], ␤-blockers [66], calcium channel blockers [67], nonsteroidal anti-inflammatory drugs [68], and dexamethasone), nocturnal light [69 -71], hepatic metabolism, activation of the hypothalamo-pituitary-adrenal axis [72,73], and use of opioid analgesics [74] may all affect postoperative melatonin secretion. Whether reduced endogenous secretion of melatonin after surgery has a negative effect on the oxidative status and results in increased morbidity remains to be investigated.…”
Section: Surgery Circadian Rhythm Disturbances and Melatoninmentioning
confidence: 99%